Management of the Madrasah Diniyah Takmiliah Education Development Strategy (Quantitative Description Research Study in Suranenggala District, Cirebon) - Sya’roni, Sya’roni; Kambali, Kambali; Suklani, Suklani (al-Afkar, Journal For Islamic Studies, 2025)
Management strategies in the development of education in madrasas play an important role in improving the quality of educational institutions and their relevance in facing the challenges of globalization and modernization. This research aims to analyze the strategies implemented by madrasas in developing education, including improving the curriculum, competency of teaching staff, and improving the welfare of teaching staff. The research was carried out with a quantitative approach that focused on collecting and analyzing numerical data to identify patterns, relationships or comparisons within certain populations in the Diniah madrasah in the Suranenggala sub-district, Cirebon Regency. The research results show that the development of education in madrasas is carried out through several main strategies: first, improving the quality of the curriculum by integrating religious material; second, recruitment and development of teacher competency to increase the professionalism of teaching staff; and third, strategies to improve the welfare of teaching staff and physical madrasa facilities. However, there are several obstacles, such as limited teacher educators who are competent in their fields, financial support and parental support for early madrasah education, which hinder the implementation of this strategy. This research recommends continued support from the government and community to maximize strategic efforts in developing quality madrasah.